Evidence that Memantine Reduces Chronic Tinnitus Caused by Acoustic Trauma in Rats - Zheng, Yiwen; McNamara, Emily; Stiles, Lucy; Darlington, Cynthia; Smith, Paul (Frontiers in Neurology, 2012)
Subjective tinnitus is a chronic neurological disorder in which phantom sounds are perceived. Increasing evidence suggests that tinnitus is caused by neuronal hyperactivity in auditory brain regions, either due to a decrease in synaptic inhibition or an increase in synaptic excitation. One drug investigated for the treatment of tinnitus has been the uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, memantine, although the evidence relating to it has been unconvincing to date. We re-investigated the effects of memantine on the behavioural manifestations of tinnitus induced by acoustic trauma (a 16 kHz, 110 dB pure tone presented unilaterally for 1 h) in rats. We used a conditioned lick suppression model in which lick suppression was associated with the perception of high frequency sound resembling tinnitus and a suppression ratio (SR) was calculated by comparing the number of licks in the 15 sec period preceding the stimulus presentation (A) and the 15 sec period during the stimulus presentation (B), i.e, SR = B / (A + B). Acoustic trauma resulted in a significant increase in the auditory brainstem-evoked response (ABR) threshold in the affected ear (P ≤ 0.0001) and a decrease in the SR compared to sham controls in response to 32 kHz tones in 5 out of 8 acoustic trauma-exposed animals. A 5 mg/kg dose of memantine significantly reduced the proportion of these animals which exhibited tinnitus-like behaviour (2/5 compared to 5/5; P ≤ 0.006), suggesting that the drug reduced tinnitus. These results suggest that memantine may reduce tinnitus caused by acoustic trauma.